Neuro-Pedagogical Digital Product Design: Fostering Early Childhood Religious Moderation (ECRM) via Interactive Mobile Game Blueprint - Suadi, Suadi; Bustomi, Abu Amar; Santiago, Paulo Vitor da Silva (Jurnal Pendidikan Anak, 2025)
This study addresses the critical need for innovative digital media to instill Religious Moderation (ECRM) and Islamic values ​​early, contrasting traditional methods with the pervasive digital environment young children inhabit. The primary objective is to develop a scientifically grounded ECRM Conceptual Framework and produce a detailed Digital Product Blueprint for an Interactive Mobile Game, aligning with CEJ's focus on Holistic & Islamic ECCD and Neuro-Pedagogy. Employing the Research & Development (R&D) approach using the 4D model (Define-Design), the research scope halts at the design stage. The Define phase encompasses a needs assessment to analyze the alignment between existing Islamic curriculum, the necessity for early radicalism prevention, and young children's high digital exposure. Data were collected via document analysis (e.g., of the current PAI curriculum and international journals on digital literacy), supported by existing research on the integration of digital tools in religious education. The Design phase involved drafting the ECRM Mobile Game blueprint, detailing game mechanics, narrative flow (storyboard), and UI/UX optimized for neuro-pedagogical principles to foster affective and behavioral growth. This ensures the output is an expert-reviewed, technology-based product blueprint rooted in Islamic educational objectives. The key finding is the production of a validated ECRM Mobile Game Blueprint, ready for prototyping and future effectiveness testing.